From Synaptic Dysfunction to Neuroprotective Strategies in Genetic Parkinson’s Disease: Lessons From LRRK2 - Mancini, Andrea; Mazzocchetti, Petra; Sciaccaluga, Miriam; Megaro, Alfredo; Bellingacci, Laura; Beccano-Kelly, Dayne A.; Di Filippo, Massimiliano; Tozzi, Alessandro; Calabresi, Paolo (Frontiers in Cellular Neuroscience, 2020)
The pathogenesis of Parkinson’s disease (PD) is thought to rely on a complex interaction between the patient’s genetic background and a variety of largely unknown environmental factors. In this scenario, the investigation of the genetic bases underlying familial PD could unveil key molecular pathways to be targeted by new disease modifying therapies, still currently unavailable. Mutations in the leucine-rich repeated kinase 2 (LRRK2) gene are responsible for the majority of inherited familial PD cases and can also be found in sporadic PD, but the pathophysiological functions of LRRK2 have not yet been fully elucidated. Here, we will review the evidence obtained in transgenic LRRK2 experimental models, characterized by altered striatal synaptic transmission, mitochondrial dysfunction, and α-synuclein aggregation. Interestingly, the processes triggered by mutant LRRK2 might represent early pathological phenomena in the pathogenesis of PD, anticipating the typical neurodegenerative features characterizing the late phases of the disease. A comprehensive view of LRRK2 neuronal pathophysiology will support the possible clinical application of pharmacological compounds targeting this protein, with potential therapeutic implications for patients suffering from both familial and sporadic PD.